Allyl isothiocyanate attenuates LED light-induced retinal damage in rats: exploration for the potential molecular mechanisms. (2nd October 2021) - Orhan, Cemal; Gencoglu, Hasan; Tuzcu, Mehmet; Sahin, Nurhan; Ozercan, Ibrahim Hanifi; Morde, Abhijeet Ashok; Padigaru, Muralidhara; Sahin, Kazim
Abstract: Purpose: Environmental light pollution due to artificial light may increase the rate and severity of retinal diseases, and plant-based nutritional interventions with antioxidant properties have the potential to reverse this phenomenon. We aimed to investigate the potential effects of allyl isothiocyanate (AITC) against white light-emitting diode (LED)-induced retinal degeneration (RD) in the rats. Methods: Twenty-eight male rats were allocated as: (i) Control, (ii) LED, (iii) LED + AITC (10 mg/kg BW), (iv) LED + AITC (20 mg/kg BW). Rats were administered with AITC for 28 days, followed by two days of intense environmental LED light (750 Lux ) exposure to the eyes. Animals were sacrificed immediately at the end of the study, then the blood and eyeballs were taken for the biochemical, western blotting, and histopathology examinations. Results: AITC lowered the serum and retina malondialdehyde (MDA) levels while significantly ( p <  0.05) improving the retinal antioxidant enzyme activities in a dose-dependent manner. AITC improved retinal and outer nuclear layer (ONL) thickness as compared to the LED group ( p <  0.05). AITC increased the levels of Bax, caspase-3, HO-1, GAP43, and VEGF, while decreasing IL-1β, IL-6, NF-κB, Bcl-2, GFAP, Grp78, activating ATF4 and ATF6 as compared to the LED group ( p <  0.05). Conclusion: In conclusion, four weeks of AITC administration to the rats showed specific protective effects against two days of intense LED light-induced retinal damage; through antiinflammatory, antioxidant, anti-apoptotic, and modulating mitochondrial metabolic pathways.